2017
DOI: 10.1002/pits.22018
|View full text |Cite
|
Sign up to set email alerts
|

Academic Leaderships Views of School Psychology and Black Students: The Case of Historically Black Colleges and Universities

Abstract: The purpose of this study was to understand academic leadership's views of the field of school psychology. This is the first study that has attempted to incorporate the views of historically Black college and university (HBCU) Psychology Department Chairs' regarding the field of school psychology and the potential development of school psychology programs at HBCUs. The results indicated that Department Chairs at HBCUs are not recommending the field of school psychology to their students based on a variety of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 23 publications
0
16
0
Order By: Relevance
“…Acknowledging the importance of racial diversity, school psychology has an emerging research base related to the recruitment of people of color into school psychology programs (e.g., Beeks & Graves, ; Chandler, ; Proctor & Truscott, ; Rogers, ; Rogers & Molina, ). Interestingly, Proctor and Romano () conducted a systematic review of the school psychology recruitment research and found that much of it focuses on undergraduates and consists mostly of White participants.…”
mentioning
confidence: 99%
“…Acknowledging the importance of racial diversity, school psychology has an emerging research base related to the recruitment of people of color into school psychology programs (e.g., Beeks & Graves, ; Chandler, ; Proctor & Truscott, ; Rogers, ; Rogers & Molina, ). Interestingly, Proctor and Romano () conducted a systematic review of the school psychology recruitment research and found that much of it focuses on undergraduates and consists mostly of White participants.…”
mentioning
confidence: 99%
“…Finally, there is support in the recruitment and retention research for recruiting undergraduates from HBCUs (Chandler, 2011;Graves & Wright, 2009;Proctor & Truscott, 2013). This finding is not surprising given the incredibly talented Black students who attend HBCUs (Beeks & Graves, 2017). Historically, as can be seen from two influential psychologists-Beckham and Sumner-graduating in the same year from Lincoln University, HBCUs have produced some of the greatest thinkers in Psychology.…”
Section: Recruit Black Thinkers From Hbcus and Develop Programs At Hbcusmentioning
confidence: 99%
“…It is also noteworthy that Celeste Malone, the President-Elect of NASP (who will be the second Black person to serve as a NASP president), is the current Director of the School Psychology Program at Howard University. Throughout history, HBCUs have employed committed faculty who produce graduates of high quality (Beeks & Graves, 2017).…”
Section: Graduate Programsmentioning
confidence: 99%
“…Clearly, it will take extensive and persistent individual and collective actions to overcome the systemic oppression, racism, inequities, and challenges that are present in our schools, communities, and society. We recognize that our current DEI efforts are informed by and build upon the efforts of many colleagues who have contributed tremendous leadership and scholarship aimed at advancing diversity and social justice in school psychology (e.g., Beeks & Graves, 2017;Blake et al, 2016;Bocanegra et al, 2016;Clark et al, 2012;Grapin et al, 2016;Graves & Brown-Wright, 2013;Graves & Wright, 2009;Goforth, 2016;Gross & Malone, 2019;Harris & Sullivan, 2017;Liu et al, 2019;Malone & Ishmail, 2020;Mena & Rogers, 2017;Newell et al, 2010;Noltemeyer et al, 2013;Parris et al, 2019;Proctor et al, 2014;Proctor, Kyle et al, 2018;Proctor, Nasir et al, 2018;Proctor & Romano, 2016;Proctor & Truscott, 2012Shriberg & Desai, 2014;Shriberg et al, 2008Shriberg et al, , 2011Shriberg et al, , 2013Smith et al, 2016;Song et al, 2019;Sullivan et al, 2015Sullivan et al, , 2020Sullivan & Proctor, 2016;Truscott et al, 2014;Vega et al, 2018;Zhou et al, 2004). We invite each of our colleagues to join us in ongoing and upcoming actions to Be the Change in advocating for and advancing DEI in school psychology.…”
Section: Impact Statementmentioning
confidence: 99%